Effect of Education Program on Knowledge and Self-care Behaviors of Patients with Retinal Detachment Who Underwent an Operation of Gas or Silicone Oil Injection: ผลของโปรแกรมการสอนต่อความรู้และพฤติกรรมการดูแลตนเองของผู้ป่วยจอตาลอกที่ได้รับการผ่าตัดด้วยวิธีการฉีดแก๊สหรือน้ำมันซิลิโคนเข้าตา - Paspisanu, Chantawan; Panyawan, Issaree (Journal of Nursing and Health Sciences Nakhon Phanom University, 2024)
This quasi-experimental research the objectives were to compare knowledge scores within the experimental group and between the experimental and control groups after implementing an educational program for retinal detachment patients who underwent a surgery of gas or silicone oil injection. The sample consisted of 48 retinal detachment patients receiving treatment at the Ophthalmology Ward of Maharaj Nakorn Chiang Mai Hospital, divided into experimental and control groups of 24 patients each. Data were collected from January to June 2024. The instruments used included a personal information questionnaire, a knowledge test, a behavioral intention questionnaire, and a teaching program. Data were analyzed using descriptive statistics and appropriate inferential statistics. The results showed that, after receiving the teaching program, the knowledge level of the experimental group increased significantly, with all patients in the experimental group (100%) having good knowledge compared to 16.67% before the experiment. The control group showed only slight changes, with the number of patients having good knowledge increasing from 16.67% to 45.83%. The mean scores for knowledge and self-care behaviors after the experiment were significantly different between the two groups (p < 0.001 and p = 0.05, respectively), with the experimental group having higher average scores than the control group. This research demonstrates the effectiveness of the educational program in enhancing knowledge and improving self-care behaviors among retinal detachment patients who underwent surgery with gas or silicone oil injection.